Cengklik Reservoir Performance and Its Role for Drought Mitigation - Yovi Hardiyanto (Journal of the Civil Engineering Forum, 2015)
Water availability problem is encountered by Cengklik Reservoir due to drought disaster in the current year. It causes irrigation water crisis over 850 hectares crop field which of 350 hectares were not cultivated. The risk that must be faced by farmers is decrease in potential productivity, losses about more than 2.5 billion. Therefore, it needs technical solution to reduce this drought disaster risk. To obtain an alternative solution against water availability problem for drought disaster mitigation, this research used optimization of reservoir standard operating simulation. It applies field area of rice or Palawija at the second and/or the third cultivation season as decision variable, maximum productivity value as objective function, irrigation water demand as parameter depending on specified alternative crop pattern and schedule, and several constraints comprising 100% of reservoir reliability, all field is irrigated at the first and second season in which maximum non-irrigated crop field at the third cultivation season are 300 hectares. The tool used to conduct optimization was Microsoft Excel software. The result showed that crop pattern considered as an alternative solution against water availability problem in Cengklik reservoir is paddy-paddy-maize at the early of November II cultivated over 433 hectares and 1524 hectares. Risk reduction reached 9.33% in term of reservoir reliability, 23.61% in term of irrigated area, and 27.29% in term of vulnerability towards water availability crisis.